Eigenschaften biologischer Materialien zur Simulation menschlicher Bewegung Funktionell-anatomische Grundlagen und Materialeigenschaften zur Erstellung dreidimensionaler Körpermodelle im Computer - Lohmann, S. (Universität Konstanz, Fachbereich Geschichte und Soziologie, 2005)
The analysis of stress and strain of human body and his parts becomes more complex and more realistic with the increasing improvment of computer technology. Whereas in 1960 a body modell were built out of 15 geometrical segments, multi segmented body modells today consist of bodis, which are constructed from CT-Imaging. To get authentical bodies for a multisegmental body modell we scanned the bones of a human skelteton by means of a 3D-laser scanner and rekonstructed the skeleton in SolidDynamics 6.2. Research obect of this publication is to collect basic physical data of human bones, muscles, tendons, positions of structures within the skeleton, anthropometrical data and aspects of functional anatomy to create a authentical multisegmental body modell of human and to simulate movement.